PENINGKATAN AKTIVITAS BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN MODEL SCRAMBLE KELAS V - Supiandi, Supiandi; Sabri, Tahmid; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research problem is whether there is an increase in student learning activities in the learning of Citizenship Education using the Scramble model in Class V State Primary School 41 Pontianak Utara. Research properties increase student learning activities using the scramble model.The method used in this research is descriptive method. Data technique used is the technique of direct observation and measurement with data collection tool that is Student Activity Sheet. Setting research with subject Teachers / Researchers and students class V Equipment 25 students.Results of the III cycles of the study are: 1) the ability of teachers in accordance with the learning cycle I with a value of 2.45 with good enough category, Cycle II increased 0.29 to 3.15 which belonged to either category. While Cycle III increased 0.8 to 3.95 and entered in very good category. 2) the ability of teachers advanced learning cycle I started with a value of 2.34 with good enough category, Cycle II has increased 0.94 so that 3.28 into the good category. While in Cycle III also increased 0.69 to 3.97 and entered very good category. 3) Student learning activity cycle I the percentage of student learning activity by 37.6% with low category increased 27.2% in cycle II to 64.8% with medium category and in the third cycle increased 24% to 88.8% high. Keywords: Student Learning Activities, Model Scramble, Citizenship Education.